Real-life outcome after failure to venetoclax and hypomethylating-based therapy for acute myeloid leukemia - Carlos Jiménez-Vicente; Iago Arribas; Helena Pomares; Guillermo Ramil; Sandra Castaño-Diez; Amanda Isabel Pérez-Valencia; Antonella Luciana Sturla; Mònica López-Guerra; Alexandra Martinez-Roca; Inés Zugasti; Francesca Guijarro; Albert Cortés-Bullich; et al. (Haematologica)
Not available.